Microenvironment and endocrine resistance in breast cancer: Friend or foe? - Recouvreux, Sol (2015)
Breast cancer affects one in eight women around the world. Seventy five percent of these patients have tumors that are estrogen receptor positive and as a consequence receive endocrine therapy. However, about one third eventually develop resistance and cancer reappears. In the last decade our vision of cancer has evolved to consider it more of a tissuerelated disease than a cell-centered one. This editorial argues that we are only starting to understand the role the tumor microenvironment plays in therapy resistance in breast cancer. The development of new therapeutic strategies that target the microenvironment will come when we clearly understand this extremely complicated scenario. As such, and as a scientific community, we have extremely challenging work ahead. We share our views regarding these matters.